2015
DOI: 10.2471/blt.14.139535
|View full text |Cite
|
Sign up to set email alerts
|

Increasing organ donation by presumed consent and allocation priority: Chile

Abstract: Chile, a middle-income country, recently joined Israel and Singapore as the world’s only countries to require reciprocity as a precondition for organ transplantation. The Chilean reform includes opt-out provisions designed to foster donation and priority for organ transplantation for registered people. Although the reform has had serious difficulties in achieving its mission, it can be reviewed by other countries that seek to address the serious shortage of organs. As increased organ donation can substantially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 17 publications
0
49
0
4
Order By: Relevance
“…The sudden pressure of this change spurred public unease and millions of opt-outs. However, surveys showed that 70% of people did not fully understand the new law [5]. We can be reasonably sure that this will not be the case in Canada.…”
Section: Drawbacks Of the 'Opt-out' Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…The sudden pressure of this change spurred public unease and millions of opt-outs. However, surveys showed that 70% of people did not fully understand the new law [5]. We can be reasonably sure that this will not be the case in Canada.…”
Section: Drawbacks Of the 'Opt-out' Systemmentioning
confidence: 99%
“…In general, this idea is thought to promote organ donation. Many studies have been dedicated to confirming this hypothesis [5,6]. However, one must be careful when com-paring donor and transplant rates in different countries.…”
Section: Arguments For An 'Opt-out' Systemmentioning
confidence: 99%
See 3 more Smart Citations